Production lead time improvement through lean manufacturing. Issue 1 (31st December 2022) - Gebeyehu, Sisay G.; Abebe, Muluken; Gochel, Amdework
Abstract: Lean manufacturing (LM) practices and tools have played vital role in several manufacturing industries to enhance the competitive edge in in the global market. The purpose of this paper is to use the lean principles, practice and tools in Hibret Manufacturing & Machine Building Industries (HMMBI) in Ethiopia. The existence of high production lead time is getting the basic problem for HMBI that is why this research gives more attention. The study aims to improve the production lead time by minimizing non-value adding activities associated with several resources in the process. Both qualitative and quantitative data collection methods are used. The process time and floor layout are studied and mapped using Value Stream Mapping, and Spaghetti Diagram to identify wastes. The result shows that production lead time, work in process (WIP), non-value adding time (waiting time) and total distance traveled are reduced by 23.66%, 8.6%, 37.74%, 61.2% respectively. Finally, the process cycle efficiency is improved by 25.59%. The study is found significant for Hibret Manufacturing & Machine Building Industries (HMMBI) and for similar manufacturing industries.